Razvoj, rast in zorenje možganov - Bregant, Tina (Psihološka obzorja (Ljubljana), 2012)
Longitudinal studies of healthy children enable us to explore and follow development, growth, and maturation of brain. Of high value are longitudinal psychological studies combined with magnetic resonance imaging (MRI) which can be advanced to brain morphometric and volumetric studies. In the article we present key findings related to brain development and provide the insight into some aspects of child development. We focus on developmental key periods including the prenatal period. We describe the processes which influence the brain structure. Changes in white matter, regionally specific trajectories of grey matter and some subcortical structures are presented. We describe characteristics of brain functioning during development and maturation. The article gives the insight into some pivotal neuroanatomical processes which influence child behaviour.
Keywords: brain; možgani; development; razvoj; child; children; otroci; adolescents; mladostniki; magnetic resonance imaging (MRI); magnetnoresonančno slikanje (MRI)